2014
DOI: 10.1016/j.cmet.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The Cholesterol Metabolite 27-Hydroxycholesterol Promotes Atherosclerosis via Proinflammatory Processes Mediated by Estrogen Receptor Alpha

Abstract: Summary Oxysterols are cholesterol metabolites that serve multiple functions in lipid metabolism, including as liver X receptor (LXR) ligands. 27-hydroxycholesterol (27HC) is an abundant oxysterol metabolized by CYP7B1. How 27HC impacts vascular health is unknown. We show that elevations in 27HC via cyp7b1 deletion promote atherosclerosis in apoe−/− mice without altering lipid status; furthermore, estrogen-related atheroprotection is attenuated. In wild-type mice, leukocyte-endothelial cell adhesion is increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(132 citation statements)
references
References 62 publications
2
127
3
Order By: Relevance
“…Several oxysterols have been identified in humans and atherosclerotic animal models. 9,12 Although there are several nonhuman studies suggesting a detrimental role of 7-KC 35 and 27-hydroxycholesterol 36,37 on endothelial function, this study shows the association of oxysterols with endothelial dysfunction in humans. Treatment with ezetimibe was associated with the inhibition of sterol absorption and decreases of both enzymatic (intrinsic) and nonenzymatic oxysterols through the inhibition of sterol absorption.…”
Section: Cholesterol Absorption and Lipid Oxidationcontrasting
confidence: 46%
“…Several oxysterols have been identified in humans and atherosclerotic animal models. 9,12 Although there are several nonhuman studies suggesting a detrimental role of 7-KC 35 and 27-hydroxycholesterol 36,37 on endothelial function, this study shows the association of oxysterols with endothelial dysfunction in humans. Treatment with ezetimibe was associated with the inhibition of sterol absorption and decreases of both enzymatic (intrinsic) and nonenzymatic oxysterols through the inhibition of sterol absorption.…”
Section: Cholesterol Absorption and Lipid Oxidationcontrasting
confidence: 46%
“…It has been reported that long-term feeding of cholesterol to rodents may affect cerebral microcirculation [21] and induce cerebral inflammatory markers [12,22]. Also, 27OH has recently been shown to promote atherosclerosis and inflammatory changes in mice [23].…”
Section: General Conclusionmentioning
confidence: 99%
“…27HC was discovered to bind to estrogen receptors (ER) and act as a selective ER modulator (SERM) eliciting system-specific adverse effects. In the vascular wall, 27HC functioned as an ER antagonist and inhibited estrogenrelated cardioprotection (Umetani et al, 2007(Umetani et al, , 2014; Umetani and Shaul, 2011). Conversely, in breast tumors, 27HC served as a partial ER agonist and stimulated tumor growth in several mouse models of breast cancer (Nelson et al, 2013;Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%